Studying religion in Nordic newspapers : an introduction. - Taira, Teemu (2019)
This article introduces the topic of this special issue: religion in Nordic newspapers. It provides a general framework for the following four articles based on a longitudinal study of religion in Danish, Finnish, Norwegian, and Swedish newspapers by clarifying what characterizes selected 'Nordic' countries, their media spheres, and their religious landscapes. Furthermore, this article suggests that despite significant changes in the media sphere, including factual media production and consumption, there are good reasons to study religion-related media content produced by the dominant and conventional media outlets, including newspapers. However, this should not be done by isolating newspapers from society and the rest of the media. This introduction and the following articles therefore propose that the selected key concepts and debates among sociologists of religion are particularly useful in thinking about religion-related newspaper content.
jufo:3
Peri2020 ; B
Keywords: uskonto ja uskonnot; sanomalehdet; uskontososiologia; religion och religioner; dagstidningar; religionssociologi; Pohjoismaat; Norden